Validación del proceso de esterilización por calor húmedo de solución isotónica inyectable cloruro de sodio 0,9% x 1 000 ml, Lima. septiembre - noviembre del 2007 - Villegas Campos, Juan José (2008)
The purpose of the present work is to determine the sterility assurance level (SAL) of the cycle of sterilization and to verify the good functioning of the autoclave, in the specified conditions. This descriptive study, conducted over a period of eight weeks, which consisted of the Installation Qualification (IQ), was verify the facilities or the components involved in the operation autoclave. The Operation Qualification (OQ) consisted of three tests in camera without product load, in order to verify the proper functioning of the autoclave, according to the manufacturer's specifications. In the Performance Qualification (PQ) were three tests in camera with product load and served to identify colder points or slow to reach the required temperature and finally three tests of defiance, using biological indicators (BIs), with the aim of determining who succeeds in logarithmic units reduce the sterilization cycle under the autoclave conditions and with the product being studied. Being obtained that the diversion maximum of the average temperatures are found below 2,5 ° C, the heat penetration (F105 ° C) is bigger than 105, 05 minutes, except the sensor 6 in the third test is 104,7. However, microbial growth was not observed for this one and other points, which makes valid runs. According to the studies of bioburden a SAL of 10-6 excels itself. Concluding that the sterilization process for humid heat of the product in study provides the requirements and destroys the microorganisms to allowed limits. According to the studies of bioburden a SAL of 10-6 excels itself.